A MONOGRAPH OF THE GENUS DIPLODISCUS* Turcz. (TILIACEAE) - KOSTERMANS, A. J. G. H. (REINWARDTIA, 1960)
1. Seven species of the genus Diplodiscus are described, of which three (D. microlepis, D. parviflorus and D. decumbens) are new to science, and one (D. hookerianus) was formerly described as Pentace (for the description of D. decumbens cf. p. 264).2. The area of distribution of the genus covers the Malay Peninsula, Borneo and the Philippines.3. The affinities of the genus are discussed.4. A key to the species is presented.